AKOMODASI KOMUNIKASI DALAM INTERAKSI ANTAR BUDAYA ETNIS TIONGHOA DAN MELAYU (STUDI DI DESA PANIPAHAN KECAMATAN PASIR LIMAU KAPAS KABUPATEN ROKAN HILIR PROVINSI RIAU) - Ahsanul Furqan; Welly Wirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Panipahan Village is one of the villages in Pasir Limau Kapas District, Rokan Hilir Regency. The original inhabitants of Panipahan village are ethnic Malays. In addition, Panipahan village is also inhabited by immigrants, one of the most immigrants is ethnic Chinese. The ethnic Chinese in Panipahan Village live in groups and have difficulties in interacting with the ethnic Malay community. Thus, the interaction between the two is still very limited. This study aims to determine the strategies for convergence, divergence and over-accommodation between ethnic Chinese and Malay ethnic cultures in Panipahan Village, Pasir Limau Kapas District, Rokan Hilir Regency, Riau Province. This research is a type of qualitative descriptive research that focuses on communication accommodation. The research data were obtained through a process of observation, in-depth interviews and documentation with 6 informants who were selected using a purposive technique with the criteria of having lived more than 5 years, aged over 25 years and willing to become informants in this study. The analysis technique used is to follow the concept given by Miles and Huberman with the stages namely data reduction, presenting data, verification and drawing conclusions. The technique of checking the validity of the data used is in the form of triangulation and extension of participation. The results of the study are that Chinese ethnicity mixes Malay with Indonesian when interacting with Malay ethnic groups. Later, many Chinese ethnic traditions have been adapted to Malay culture, such as wedding customs, funerals, buildings and also the tradition of burning barges (convergence). The Chinese ethnic use Indonesian when interacting with the Malays and still show their original cultural identity (divergence). In communicating, it is precisely the Malay people who use a distinctive greeting when interacting with ethnic Chinese (excessive accommodation).